Cholinesterase activity in the caddisfly Sericostoma vittatum: biochemical enzyme characterization and in vitro effects of insecticides and psychiatric drugs - Pestana, João L. T.
Sericostoma vittatum is a caddisfly species, endemic to the Iberian Peninsula, proposed as a biomonitor species for lotic ecosystems. Since inhibition of cholinesterases[U+05F3] (ChE) activity has been used to evaluate the exposure of macroinvertebrates to organophosphates and carbamate pesticides, this work intended to characterize the ChE present in this species so their activity can be used as a potential biomarker of exposure. Biochemical and pharmacological properties of ChE were characterized in this caddisfly species using different substrates (acetylthiocholine iodide, propionylthiocholine iodide, and butyrylthiocholine iodide) and selective inhibitors (eserine sulfate, BW284c51, and iso-OMPA). Also, the in vitro effects of two insecticides (carbaryl and chlorantraniliprole) and two psychiatric drugs (fluoxetine and carbamazepine) on ChE activity were investigated. The results suggest that S. vittatum possess mainly AChE able to hydrolyze both substrates acetylthiocholine and propionylthiocholine since: (1) it hydrolyzes the substrate acetylthiocholine and propionylcholine at similar rates and butyrylthiocholine at a much lower rate; (2) it is highly sensitive to eserine sulfate and BW284c51, but not to iso-OMPA; and (3) its activity is inhibited by excess of substrate, a characteristic of typical AChE. in vitro inhibitions were observed only for carbaryl exposure while exposure to chlorantraniliprole and to relevant environmental concentrations of psychiatric drugs did not cause any significant effect on AChE activity. This study suggests that AChE activity in caddisflies can indeed be used to discriminate the effects of specific insecticides in monitoring programs. The use of non-target species such as caddisflies in ecotoxicological research in lotic ecosystems is also discussed.